Effect Of Green HRM And Work Environment On Job Satisfaction: Evidence From PERUMDA Tirta Mangkaluku Palopo, Indonesia - Andi putri Andini; Muhammad Kasran; Halim Usman (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This Study Aims To Analyze The Influence Of Green Human Resource Management And Employee Work Environment On Job Satisfaction At Perumda Tirta Mangkaluku, Palopo City. The Problem Raised Is How Ghrm Practices And Work Environment Conditions Can Contribute To Increasing Job Satisfaction. Methodology: This Study Uses a Quantitative Method With a Multiple Linear Regression Approach. Data Were Obtained Through Distributing Questionnaires To 76 Respondents, Then Analyzed Using Spss. Results: The Results Of This Study Indicate That The Research Instrument Is Valid And Reliable. The Classical Assumption Test Has Been Met, This Shows That Ghrm Has a Positive And Significant Effect On Job Satisfaction With a T-Count Value Of 4.153 > 1.993 And a Significance Of 0.000 < 0.05. Likewise, The Work Environment Has a Positive And Significant Effect With a T-Count Value Of 3.068 > 1.993 And a Significance Of 0.003 < 0.05. Simultaneously, Both Independent Variables Significantly Influence Job Satisfaction, With An F Value Of 40.318 > F Table 3.1239, And a Significance Level Of 0.000. The Coefficient Of Determination Shows That Ghrm And Work Environment Explain 52.5% Of Job Satisfaction, While The Remaining 47.5% Is Influenced By Factors Outside The Research Model. Findings: The Findings Confirm That Both Ghrm And Work Environment Are Critical Determinants Of Job Satisfaction, With Ghrm Emerging As The More Dominant Factor. Novelty & Originality: The Novelty Of This Study Lies In Its Focus On Ghrm Implementation Within a Regional Water Utility Company In Palopo City, a Context Rarely Examined In Prior Research. Its Originality Emerges From The Simultaneous Testing Of Ghrm And Work Environment In The Indonesian State-Owned Enterprise Sector. Conclusions: The Study Concludes That Enhancing Ghrm Practices And Improving Work Environment Conditions Are Essential Strategies For Increasing Employee Job Satisfaction. Type Of Paper: This Paper Is An Empirical Research Paper.